2005
DOI: 10.1161/01.cir.0000164236.19860.13
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ABCA1-Mediated Cholesterol Efflux and Accelerated Atherosclerosis in Apolipoprotein E–Deficient Mice Lacking Macrophage-Derived ACAT1

Abstract: Background— Macrophage acyl-coenzyme A:cholesterol acyltransferase 1 (ACAT1) and apolipoprotein E (apoE) have been implicated in regulating cellular cholesterol homeostasis and therefore play critical roles in foam cell formation. Deletion of either ACAT1 or apoE results in increased atherosclerosis in hyperlipidemic mice, possibly as a consequence of altered cholesterol processing. We have studied the effect of macrophage ACAT1 deletion on atherogenesis in apoE-deficient (apoE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 50 publications
0
45
1
Order By: Relevance
“…Interestingly, the modulation of cholesterol transport in macrophages affects the expression of molecules implicated in efferocytosis such as MFGE8. 49 Moreover, using immunohistochemistry, we have demonstrated a decrease of MFGE8 protein expression in macrophages around the necrotic core. 50 These data suggest that changes in macrophage phenotype during atherogenesis and foam cell formation might substantially alter efferocytosis.…”
Section: Impaired Efferocytosis In Atherosclerosismentioning
confidence: 78%
See 1 more Smart Citation
“…Interestingly, the modulation of cholesterol transport in macrophages affects the expression of molecules implicated in efferocytosis such as MFGE8. 49 Moreover, using immunohistochemistry, we have demonstrated a decrease of MFGE8 protein expression in macrophages around the necrotic core. 50 These data suggest that changes in macrophage phenotype during atherogenesis and foam cell formation might substantially alter efferocytosis.…”
Section: Impaired Efferocytosis In Atherosclerosismentioning
confidence: 78%
“…47 Moreover, Ogden et al showed that IgM is required for optimal complement dependent efferocytosis of ACs. 48 Besides competitive inhibition with oxLDL, oxidative stress 44 and transformation into foam cells 49 also impair the capacity to engulf apoptotic debris. Interestingly, the modulation of cholesterol transport in macrophages affects the expression of molecules implicated in efferocytosis such as MFGE8.…”
Section: Impaired Efferocytosis In Atherosclerosismentioning
confidence: 99%
“…Experimentally, in a mouse model for atherosclerosis, partial inhibition of ACAT1 activity by an ACAT1-specific inhibitor K604 reduced the CE content at the atherosclerogenic lesions and caused regression of the atherosclerotic plaques without altering the overall serum cholesterol levels in the treated animals (46). However, complete inhibition of ACAT1 by gene inactivation in macrophages produced severe cytotoxicity and enlarged the atherosclerotic lesions (47,48). In addition, when rodent macrophage cell lines were grown under conditions with minimal cellular cholesterol efflux (a situation that may occur in advanced atherosclerotic lesions), addition of isotype nonspecific ACAT inhibitors to the cells caused undesirable build up of cellular free (unesterified) cholesterol and led to the cells undergoing apoptosis (49).…”
Section: Discussionmentioning
confidence: 99%
“…1,16 This is in agreement with a recent finding showing a downregulation of Mfge8 mRNA expression in a subset of free cholesterol-loaded macrophages. 17 In addition, apoptotic cell death as detected by TUNEL staining occurred more frequently in areas with low Mfge8 expression in advanced human lesions (Data Supplement Figure III).…”
Section: Mfge8 Is Expressed In Normal and Atherosclerotic Human Arteriesmentioning
confidence: 93%